Ethnomathematical applied juniors grade from two public educational institutions in Lima, the start and end of the year 2013 - Nuñez Alvarado, Milagros (2015)
This research is descriptive ex post facto. In this it was proposed to determine the effects of Ethnomathematics that was applied as a strategy in two samples of 30 children with an average of 7.5 years in the districts of San Juan de Miraflores and Rimac, the start and end of the 2013. They are attending same classrooms where training programs were implemented in developing strategies for mathematics. In turn, we sought to describe the levels of achievement of this troubleshooting. Highest score was determined in the sample of San Juan de Miraflores at the beginning of the investigation. At the end it was observed differences were not signif¬icant (p < 0.01). 50% of subjects reached this level of achievement in solving problems, and 15% reached the process level by the end of the application of this strategy.